Tinjauan Yuridis Pengajuan Permohonan Peninjauan Kembali pada Perkara Pidana dalam Sistem Hukum Indonesia - I Made Widi Adi Peremana; A. A. Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Warmadewa Press, 2020)
The study of this research is the submission of requests for reconsideration in criminal cases in the Indonesian legal system which became a polemic after the issuance of the Constitutional Court Decision Number 34 / XI-PUU / 2013 and Circular Letter of the Supreme Court (SEMA) Number 7 of 2014 concerning Submission of Reappeals in Cases Criminal. The research objectives to be achieved, in this case, are the regulation of legal reconsideration efforts in Indonesia and the procedure for submitting a request for review in the Indonesian system. Researchers use a normative juridical approach or library research or doctrinal legal research which can be interpreted as legal research by examining library materials and secondary materials. This study illustrates that the regulations for reconsideration in the legal system in Indonesia are based on various regulations, namely Law Number 8 of 1981 concerning the Criminal Procedure Code, Law No. 3 of 2009 concerning the Supreme Court, Law no. 48 of 2009 concerning Judicial Power, Circular Letter of the Supreme Court of the Republic of Indonesia No. 7 of 2014 concerning Review of Criminal Cases and Submission of Reconsiderations at this time refers to the provisions of the Circular Letter of the Supreme Court of the Republic of Indonesia No. 7 of 2014 concerning Reconsideration in Criminal Cases.